The Review of the International Voices on the Responses of the Worldwide School Closures Policy Searching during Covid-19 Pandemic - Sarjdana Orba Manullang; Erwinsyah Satria (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
This article was to determine the voice of the international community in responding to the challenges of school closure policies during the 2019 Covid-19 pandemic. Effort to break the chain transmission of Covid-19 was believed to be closely related to the closure of all business activities including schools around the world. In order to understand the impacts and challenges of school closure, a series of critical searches were undertaken on various online sources, for instance news updates publications, practitioners, and school reactions to unplanned global policies to obligate students learning from home. The collecting data was analyzed using a qualitative phenomenological approach and in-depth interpretation to at the collective voice fulfills the reliability and validity of the research problem. The findings indicated that 16 international voices from different perspectives show relatively deep concern about school closures. Voices from these discussions were matched with existing questions and knowledge about difficulties resulting from school closures. The findings of this study can be categorized into three votes; First are voices in support of the national school closure policy. Second, questioning national policies without prior data. Third, there is concern that families face serious challenges in supporting children learning from home with low facilities and the ability to handle student needs. Therefore, these voices would provide essential insights for further decision-making regarding community school participation in supporting of government in fighting the coronavirus epidemic. Hence, a similar study was needed as additional research evidence that helps the government anticipate the spread of this deadly virus, especially in countries and regions experiencing different impacts. Keywords: School Closure Policy in Covid-19, Learning from Home Policy, Covid-19